Happiness at Work of Employees in State-Owned General Company and Start-Up Company - Batubara, Megawati; Meithalia, Karissa; Marthatianty, Inge Foresta (Universitas Muhammadiyah Metro, 2022)
The topic of happiness at work cannot be separated from the aspects of the workplace, work environment, and job characteristics which have an essential role in shaping work happiness. Considering the importance of these aspects, there are differences in the types of work from one job to another are one of the causes that can lead to differences in happiness in the workplace. In Indonesia, the types of work that are pretty different are state-owned public companies and start-up companies. The fundamental differences are in almost all aspects of the organization, some of which are the way of interacting with colleagues and superiors, the intensity of using gadgets and information technology, salaries, facilities, and working hours. This research is non-experimental quantitative research, with a sampling approach, a non-probability sampling with a convenience sampling technique. Ninety-eight employees from a state-owned public company and 69 from a start-up company were collected by self-administered questionnaires. Self-administered questionnaires were collected from the employees. The results showed that the level of happiness at work of employees in the state-owned public company and start-up company was at the same level, slightly happy (M = 4.2 and M = 4.79). The same result is identified for the work's dimension, slightly happy (M = 4.64 and M = 4.91). The start-up shows a higher value between these two companies than the state-owned public company. This result does not differ from other companies, such as public universities, small and medium-sized enterprises, and nurses from private hospitals.